School cooperative and youth development: A case study of SMK Taman Tasik, Ampang, Selangor / Nur Ain Mohmad Zam - Nur Ain , Mohmad Zam (2020)
In the effort to develop future generations, cooperative entrepreneurship plays a significant role. This type of entrepreneurship increases its members ' economic and social interests and brings significant benefits to the community and society. Co-operative is a prominent way to generate job opportunities and reduce unemployment without relying on wage jobs, especially among young people, due to capital sharing and low risks when starting a business. The Malaysian Ministry of Education (MOE) has implemented school cooperatives since 1968 in fostering the entrepreneurial spirit, which seeks to promote entrepreneurial experiences and youth development. Hence, the primary purpose of this paper is to highlight the current school cooperative practices in Malaysian secondary schools by reviewing the impact of the activities of school cooperatives in instilling youth entrepreneurial knowledge and motivation. The purpose of this concept paper is also to raise awareness of the importance of school cooperatives in Malaysia. The finding of this study, cooperative members acknowledge the important roles of school cooperative towards youth development. Moreover, school cooperative benefited to youth in the aspects of preparedness for personal development for instance develop talents and potential, build human capital and self-confidence. This study discovered numerous problems faced by school cooperative such as time constraint, weaknesses in management and lack of awareness as school cooperative members. Apart from that school cooperative should do improvement in organization and management based on the suggestions made by the cooperative members. The results of this study will be helpful for future studies to the collection of knowledge on youth development through school cooperative.